Discourse analysis of Elementary School Science 6 as basis for prototype reading comprehension materials in English for science - Pascual, Flora Ancheta 1946-
The main purpose of this study is to make a discourse analysis of Elementary School Science 6 to determine the rhetorical patterns found in the texts. The rhetorical process chart formulated by Selinker, Lackstrom and Trimble was used as the basis of classification in the analysis. The rhetorical patterns or discourse functions which were frequently found in the texts served as the basis for formulating instructional materials for developing skills in reading comprehension specifically for such types of rhetorical patterns.
Mimeographed.
Thesis (M.Ed.)--University of the Philippines, Quezon City
Vita
Keywords: University of the Philippines -- Science Education Center; Elementary School Science 6.; Discourse analysis; Science -- Study and teaching (Elementary) -- Philippines; Science -- Textbooks. -- Philippines